Exploring employees’ subjective experience of psychological empowerment after adopting Artificial Intelligence technology - Macnab-Holding, Cuan Selkirk (Stellenbosch : Stellenbosch University, 2024)
Thesis (MCom)--Stellenbosch University, 2024.